The Relationship Between Artificial Intelligence Dependency Behavior and Critical Thinking Skills of Grade XII Students at State Vocational High School 9 Padang - Melanie Putria Syahcorina; Linda Fitria; Yuliawati Yunus (Jurnal Counseling Care, 2025)
The integration of artificial intelligence (AI) into education has transformed learning processes by providing efficiency, personalization, and instant access to knowledge. However, excessive reliance on AI may weaken students’ intellectual autonomy and hinder the development of higher-order cognitive skills. While global studies highlight AI’s potential to foster critical thinking when embedded in reflective tasks, little is known about its impact on vocational high school students in developing contexts. This study examines the relationship between AI dependency and critical thinking among 190 twelfth-grade students at Vocational High School 9 Padang, Indonesia. Using a quantitative correlational design with purposive sampling, data were collected through a validated and reliable Likert-scale questionnaire and analyzed using parametric statistics (Kolmogorov–Smirnov test, linearity test, and Pearson’s correlation). Results indicate that both AI dependency (M = 43.46; SD = 9.89) and critical thinking (M = 51.09; SD = 7.30) were at moderate levels. However, correlation analysis revealed no significant relationship between AI dependency and critical thinking (r = 0.066, p = 0.365). These findings suggest that AI dependency does not inherently contribute to critical thinking development in vocational education. Theoretically, this study extends global discourse by emphasizing contextual differences in AI usage across educational levels. Practically, it underscores the need for balanced pedagogical strategies that leverage AI as a scaffold for reasoning, reflection, and problem-solving rather than as a shortcut for task completion.